2016
DOI: 10.1186/s13054-016-1301-x
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte programmed death ligand-1 expression after 3–4 days of sepsis is associated with risk stratification and mortality in septic patients: a prospective cohort study

Abstract: BackgroundSeptic shock is a major healthcare problem with a high mortality rate that might be caused by immunosuppression. Programmed cell death receptor-1 (PD-1) and programmed cell death receptor ligand-1 (PD-L1), which are co-inhibitory receptor molecules, participate in sepsis-induced immunosuppression. In this study, we investigated which PD-1-related molecules can be used to evaluate the risk stratification and prognosis of septic patients. Furthermore, we explored the prognostic significance of a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 30 publications
6
110
1
3
Order By: Relevance
“…This study showed some remarkable results because the inhibitory receptor expressions were comparatively low at the onset of sepsis but increased significantly over time as sepsis progressed [56, 73]. Another prospective clinical study also showed that severe sepsis caused a significant increase in PD-1 expression on CD4+ and CD8+ T lymphocytes and PD-L1 on monocytes, and furthermore monocyte PD-L1 expression on monocytes served as an independent predictor of 28-day mortality in septic shock patients [74, 75]. Shubin et al showed that BTLA expression was significantly increased on circulating CD4+ T cells and B cells in septic mice, which was associated with loss of these cells [76].…”
Section: Sepsis-induced T Cell Dysfunctionmentioning
confidence: 99%
“…This study showed some remarkable results because the inhibitory receptor expressions were comparatively low at the onset of sepsis but increased significantly over time as sepsis progressed [56, 73]. Another prospective clinical study also showed that severe sepsis caused a significant increase in PD-1 expression on CD4+ and CD8+ T lymphocytes and PD-L1 on monocytes, and furthermore monocyte PD-L1 expression on monocytes served as an independent predictor of 28-day mortality in septic shock patients [74, 75]. Shubin et al showed that BTLA expression was significantly increased on circulating CD4+ T cells and B cells in septic mice, which was associated with loss of these cells [76].…”
Section: Sepsis-induced T Cell Dysfunctionmentioning
confidence: 99%
“…As such, it can be envisioned that profiling of cellular metabolism provides a snapshot of the current immunological state of a septic patient and may be used to guide treatment. Furthermore, the programmed death 1 (PD-1) pathway appears to be of particular relevance in sepsis-induced immune suppression, and expression of PD-L1 (the ligand for PD-1) on the cell surface of monocytes is associated with risk stratification and mortality in septic patients [11]. As ex vivo addition of antibodies against PD-1 or PD-L1 restored function of monocytes, neutrophils, T cells, and natural killer (NK) cells [12], the data from clinical studies in the field of oncology that show that treatment with anti-PD-1/PD-L1 antibodies is feasible and safe [13] is of interest to the sepsis field.…”
Section: Determining the Immune Status Of Sepsis Patientsmentioning
confidence: 99%
“…These receptors have been implicated in T-cell exhaustion: unrelenting antigen exposure causes loss of T-cell function [25]. Several studies have demonstrated that these molecules are up-regulated in sepsis, making it a candidate biomarker and a candidate therapeutic target [124126]. In animal studies, inhibition of PD-1 or PD-L1, either through genetic modification or introduction of an antibody, resulted in improved survival and decreased lymphocyte apoptosis [127130].…”
Section: Five-year Viewmentioning
confidence: 99%
“…Although the sample sizes were small, two studies found that increased percentage of PD-1 class molecules were seen in non-survivors [124, 126]. Additionally, higher expression of PD-L1 and PD-L2 on monocytes at day 3–5 of illness was associated with the development of secondary nosocomial infections [125].…”
Section: Five-year Viewmentioning
confidence: 99%
See 1 more Smart Citation